Gene doping in sport - perspectives and risks - Brzezianska, E.; Domanska, D.; Jegier, A. (Biology of Sport, 2014)
In the past few years considerable progress regarding the knowledge of the human genome map has been achieved. As a result, attempts to use gene therapy in patients` management are more and more often undertaken. The aim of gene therapy is to replace defective genes in vivo and/or to promote the long-term endogenous synthesis of deficient protein. In vitro studies improve the production of human recombinant proteins, such as insulin (INS), growth hormone (GH), insulin-like growth factor-1 (IGF-1) and erythropoietin (EPO), which could have therapeutic application. Unfortunately, genetic methods developed for therapeutic purposes are increasingly being used in competitive sports. Some new substances (e.g., antibodies against myostatin or myostatin blockers) might be used in gene doping in athletes. The use of these substances may cause an increase of body weight and muscle mass and a significant improvement of muscle strength. Although it is proven that uncontrolled manipulation of genetic material and/or the introduction of recombinant proteins may be associated with health risks, athletes are increasingly turning to banned gene doping. At the same time, anti-doping research is undertaken in many laboratories around the world to try to develop and refine ever newer techniques for gene doping detection in sport. Thanks to the World Anti-Doping Agency (WADA) and other sports organizations there is a hope for real protection of athletes from adverse health effects of gene doping, which at the same time gives a chance to sustain the idea of fair play in sport.